Answer:
8x² +6x+36xy² + 27y²
Explanation:
Expand the following:
(-2 x - 9 y^2) (-4 x - 3)
(-9 y^2 - 2 x) (-4 x - 3) = (-9 y^2) (-4 x) + (-9 y^2) (-3) + (-2 x) (-4 x) + (-2 x) (-3):
-9 (-4) y^2 x - 3 (-9) y^2 - 2 (-4) x x - 3 (-2) x
-9 (-4) = 36:
36 y^2 x - 3 (-9) y^2 - 2 (-4) x x - 3 (-2) x
-3 (-9) = 27:
36 y^2 x + 27 y^2 - 2 (-4) x x - 3 (-2) x
-2 x (-4) x = -2 x^2 (-4):
36 y^2 x + 27 y^2 + -2 (-4) x^2 - 3 (-2) x
-2 (-4) = 8:
36 y^2 x + 27 y^2 + 8 x^2 - 3 (-2) x
-3 (-2) = 6:
Answer: 36 y^2 x + 27 y^2 + 8 x^2 + 6 x